2020
DOI: 10.3390/ma13081976
|View full text |Cite
|
Sign up to set email alerts
|

Concrete-Based and Mixed Waste Aggregates in Rendering Mortars

Abstract: This paper presents a study of incorporation of two types of construction and demolition waste (CDW) in rendering mortars, as aggregates at 0%, 20%, 50% and 100% (by volume). Recycled concrete aggregate (RCA) and mixed recycled aggregate (MRA) were used. The former is mainly composed of cementitious waste and the latter consists of a mixture of non-segregated wastes. The performance of the cement mortars with recycled aggregates was evaluated through an extensive experimental programme. The analysis comprised … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Regarding fine recycled aggregates (FRA) from construction and demolition waste (including recycled concrete aggregates, recycled masonry aggregates and mixed recycled aggregates) incorporated in mortars, several studies have been published [6][7][8][9]. However, the incorporation of this type of waste replacing natural aggregates and reducing cement in rendering mortars has not been researched for rendering mortars.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding fine recycled aggregates (FRA) from construction and demolition waste (including recycled concrete aggregates, recycled masonry aggregates and mixed recycled aggregates) incorporated in mortars, several studies have been published [6][7][8][9]. However, the incorporation of this type of waste replacing natural aggregates and reducing cement in rendering mortars has not been researched for rendering mortars.…”
Section: Introductionmentioning
confidence: 99%
“…There is a lot of mature research on the production of recycled coarse aggregate from crushed concrete waste or reusing solid waste in the subgrade cushion [25,26]. Previous studies have found that the old mortar attached to recycled concrete aggregate negatively affects the mechanical properties and durability of concrete containing recycled concrete aggregate [27][28][29]. The development of production technology and equipment of recycled concrete aggregate contribute to removing most of the old mortar.…”
Section: Introductionmentioning
confidence: 99%
“…Some thermal and physical properties of WP/ NP compared with sand and cement, Contreras et al[63]; Roque et al[64]; Guendouz et al[65] …”
mentioning
confidence: 99%